Black cash tax evasion in Russia: Its forms, incentives and consequences at firm level - Andrei Yakovlev (Bank of Finland, Institute for Economies in Transition (BOFIT), 1999)
This paper discusses Russia's "black cash" economy.Using interviews and survey data, we examine the mechanics of several distinctly Russian tax evasion schemes and attempt a rough estimate of the scale and dynamics involved in tax evasion based on black cash.Entrepreneurs' opinions are also used to get an idea of the incentives and costs of black cash tax evasion.We next describe the apparent economic consequences of black cash tax evasion and formulate general formal conditions for successful evasion at firm level.Finally, we recommend several policy measures to reduce the incentives to such behaviour and discuss questions for future research.
URN:NBN:fi:bof-201408071919
Keywords: 330; tax evasion; informal business activity; "black cash"; Russia